Timeless seeds of advice the sayings of Prophet Muhammad, Ibn Taymiyyah, Ibn al-Qayyim, Ibn al-Jawzi and other prominent scholars in bringing comfort and hope to the soul - Abdulla, B. B. (B.B. Abdulla, 2018)
A selection of beautiful and practical pieces of advice from the Quran,the Prophet PBUH and Islam's great scholars on repentance, guidance and purification. This book is designed to serve as a source of hope and strength for those going through difficult times, while providing numerous important pieces of knowledge and guidance for all readers and all times.